Performance Assessment of some Developed Surface Irrigation Methods (Global Journal of Science Frontier Research, 2013)
Irrigation development is a gateway to increased agricultural, water and land productivity, increased household and national food security. However, irrigation development has been a major challenge in many developing countries, including Egypt. The overall objective of this study is to detect the influence of different irrigation systems on water-use efficiency, crop and soil salinity in highly soil salinity. Two techniques were applied in experiment, the first technique was siphon irrigation, and the second one was pipeline with gates. The monitored parameters were water table depth, water and soil salinity and crop yield. The total leaching water requirements was given to control the salinity and the crop production. The study revealed that the cotton crop yield was higher by 17% with gate pipeline treatment compared to siphon irrigation treatment. The total soil salinity increased in both treatments. The siphon method gives highest value of total salinity at all seasons. This method increased the salinity by 2.7% while the pipeline with gate increased the salinity by 12.9%. Convergence the value of the crop coefficient in all relations used in most stages of growth, except Penman relationship which gave the highest values.
Keywords: siphon irrigation method; pipeline with gate irrigation method; subsurface drainage; watertable management; water-table salinity; soil salinity; and c